Structural separation and access in telecommunications markets - Paul W. J. de Bijl (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper presents a basic framework to assess whether structural (vertical) separation is desirable. It is discussed within the setting of fixed telecommunications markets. From an economist's perspective, the key question that underlies the case for structural separation is: is there a persistent bottleneck? The obvious candidate is the ?local loop?, or local access network. If yes then it makes sense to compare the costs and benefits of structural separation. The framework provides a set of options that the regulator can use strategically, by using the threat of a break-up to influence an incumbent's competitive stance in the wholesale market.
Keywords: L12; L51; L4; L96; 330; Telekommunikation; Betriebsaufspaltung; Netzzugang; Telekommunikationspolitik; Theorie